Pharmaceuticals in source waters of 95 First Nations in Canada - Schwartz, Harold (Can J Public Health, 2021)
OBJECTIVES: Pharmaceuticals are emerging contaminants in the environment. Little has been published about the presence of pharmaceuticals in waterbodies nearby or on reserve land of First Nations in Canada. The objectives of this study were to (1) quantify the level of pharmaceuticals in First Nations’ surface waters, (2) calculate the human health risks of the mixtures found, and (3) measure the exposure to pharmaceuticals in First Nations’ drinking water where source water was highly contaminated. METHODS: This participatory study measured the levels of 43 pharmaceuticals from surface water samples taken at three water sampling sites chosen by the 95 participating First Nations. The sites were in proximity to recreational areas, fishing areas, drinking water sources, and/or wastewater outflows. When elevated levels of pharmaceutical mixtures were found in samples, drinking water samples were obtained and analyzed for potential pharmaceuticals. Human health risks were calculated by an established protocol. RESULTS: In total, 432 samples were collected at 302 water sampling sites (285 surface water, 11 drinking water, and 6 wastewater sites). Quantifiable levels of 35 pharmaceuticals were found in 79 of the 95 (83%) participating First Nations at 193 of the 285 surface water sites (68%). Overall, the levels found were comparable to or lower than those found in other studies in Canada and worldwide. CONCLUSION: In almost all participating First Nations, there is no human health risk from consuming surface water for drinking. However, surface water in the vicinity of major urban centres should not be used as secondary untreated water sources due to the elevated human health risk associated with exposure to the mixtures of multiple pharmaceuticals detected. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.17269/s41997-021-00499-3.